GREEN URBAN WATERFRONT MANAGEMENT CASE OF SOLO, INDONESIA - Arif Kusumawanto; Zulaikha Budi Astuti (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2014)
Solo is a city located in Central Java, Indonesia with 501.650 inhabitants in 2011. It hosted in 2010 the Asia Pacific Ministerial Conference on Housing & Urban Development (APMCHUD) as big events for this city. Besides APMCHUD is an award for Solo urban renewed images since 2005 which one of them is urban waterfront revitalization. Applying the Lourenço meta-analysis for urban growth areas which is specific in urban waterfront management, a better apprehension of the sequence of interdependencies that exist can be addressed to expand the concepts of redevelopment of urban areas. It can be done within a continuum process associated to planning and investment cycles. The applicability of the proposed model is tested by comparing the idealized evolution to the observed urban waterfront in Solo, for a period of eight years, from 2005 to 2013. This enables the discussion of conceptual issues related to the legitimizing of LCA and the present contribution. Although the complete cycle is not yet observable, it is possible to confirm that the relevant nature of this tool allows for an earlier awareness of the cycle progression anomalies and, therefore, a potentially better adjustment between observed and ideal behaviors, if these anomalies are monitored and addressed.This paper will address Solo profile and planning process, major outcomes due to urban waterfront applicability of LCA models and framework for the sustainable management.